Analisis Pendapatan Usahatani Jamur Tiram (Pleurotus Ostreatus) di Kapanewon Cangkringan Kabupaten Sleman - Tafonao, Sarti Oberlian; Kurniawati, Fitri; Purwandari, Istiti (Program Studi Agribisnis INSTIPER Yogyakarta, 2025)
Oyster mushrooms are one type of plant that is widely cultivated and has economic value and is popular with many people because it is one of the foodstuffs that is good for health. This study aims to 1) determine the characteristics of oyster mushroom farmers, 2) Determine the average income of oyster mushroom farming, 3) Determine the factors that influence the income of oyster mushroom farming. This research was conducted in Kapanewon Cangkringan, Sleman Regency on June 1-27, 2024. The method used in this study is descriptive quantitative with the snowball sampling method. The results of the study from 25 sample farmers showed that the average income of oyster mushroom farming in one period (4 months) with a total of 2000 baglogs was Rp. 9,225,875, -. Factors that influence the income of mushroom farming are work experience and labor.